103k views
0 votes
I need help with this

I need help with this-example-1
User Polkduran
by
5.3k points

1 Answer

6 votes

Answer:

Option B

Option C

Explanation:


x^(2) +2x=4

we need to divide the coefficient of x by half since it is required for completing square, this term is added and subtracted at the same time to keep the equation intact, so we have


x^(2) +2x+1-1=4

later we have


(x+1)^(2) -1=4


(x+1)^(2)= 4+1


(x+1)^(2) = 5


\sqrt{(x+1)^(2)} =√(5)

we know


\sqrt[2]{a^(2)} = abs (a)


abs(x+1)=√(5)

we have


x+1=√(5)

or


x+1= -√(5)

so we have


x=√(5)-1


x=-√(5)-1

finally


x=+- √(5)-1

The second is obtained by summing the two given equations

f(x)=8x-10

g(x)=3x+5

-----------------

f(x)+g(x)=11x-5

User Natejms
by
6.2k points